Antioxidant for heating alloy material and method for heating alloy material using the same
By using antioxidants for heating alloy materials treated with specific components and processes, the problems of oxidation and adhesion of alloy materials during long-term heating of high temperatures are solved, and excellent adhesion and oxidation resistance are achieved, improving yield and easy operation are achieved. sex.
Patent Information
- Application Number
- CN202180011845.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2021-01-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2041-01-28
AI Technical Summary
During the long-term heating of high temperatures, alloy materials are prone to oxidation and adhesion, resulting in reduced yield and complex operation. The prior art has failed to effectively solve these problems.
A new alloy material heating antioxidant is used, which consists of SiO2, Al2O3, MgO, Na2O, K2O, CaO and B2O3. The softening point is above 800°C and is processed through a specific process to reduce its wire drawing properties. Satisfies a specific chemical composition ratio to inhibit oxidation and adhesion of alloy materials.
The antioxidant exhibits excellent adhesion and oxidation resistance under high temperature and long-term heating conditions, which can effectively inhibit oxidation and adhesion of alloy materials, improve yield and simplify the operation process.
Smart Images

Figure CN115023509B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an antioxidant for heating an alloy material and a method for heating the alloy material using the antioxidant. Background Art
[0002] As an alloy material, for example, an alloy material containing Cr is known. The alloy material is manufactured by the following steps. First, molten steel is manufactured. The molten steel is cast to obtain a casting material (slab, bloom, ingot). The casting material is heated. The heated casting material is hot-worked. The intermediate material obtained by hot working is cold-worked as needed to form it.
[0003] As mentioned above, the alloy material is heated before hot working. When the alloy material is heated before hot working, a passive film is formed on the surface. The passive film is mainly a film with chromium oxide (Cr2O3) as the main body. Hereinafter, the film with chromium oxide (Cr2O3) as the main body will also be referred to as Cr2O3 film.
[0004] The Cr2O3 coating inhibits the oxidation of the alloy material. However, in the heating before hot working, the alloy material is sometimes heated at a high temperature of, for example, 1000°C or higher. When the alloy material is heated at a high temperature of 1000°C or higher, it is easy to generate an oxide scale mainly composed of Fe on the surface of the alloy material instead of the Cr2O3 coating. If an oxide scale mainly composed of Fe is generated on the surface of the alloy material, defects caused by the oxide scale mainly composed of Fe are sometimes generated on the surface of the alloy material due to the subsequent hot working. Therefore, it is expected that the oxidation of the alloy material can be inhibited even when heated at a high temperature before hot working.
[0005] For example, Japanese Patent Publication No. 2007-314875 (Patent Document 1), Japanese Patent Publication No. 2-209420 (Patent Document 2), Japanese Patent Publication No. 3-291325 (Patent Document 3), Japanese Patent Publication No. 56-026603 (Patent Document 4), Japanese Patent Publication No. 4-072019 (Patent Document 5), Japanese Patent Publication No. 4-072011 (Patent Document 6), Japanese Patent Publication No. 6-158153 (Patent Document 7), Japanese Patent Publication No. 7-062429 (Patent Document 8) and Japanese Patent Publication No. 6-198310 (Patent Document 9) disclose technologies for suppressing oxidation of alloy materials.
[0006] Patent documents 1 to 9 all disclose technologies for suppressing oxidation of alloy materials using antioxidants. Patent documents 1 to 3 envision short-term heating with a treatment time of about 20 minutes to 4 hours. Patent document 4 does not target the heating before hot working. Patent documents 5 to 8 target the alloy materials after processing.
[0007] Specifically, Patent Document 1 envisions a heat treatment with a treatment time of about 20 minutes. Patent Document 1 states that the antioxidant composition of Patent Document 1 contains a plurality of glass frits with different softening points. As a result, the antioxidant composition maintains an appropriate viscosity in different temperature ranges, and the antioxidant composition is retained on the steel surface. As a result, the generation of oxide scale is suppressed during the heat treatment.
[0008] Patent Document 2 assumes a heat treatment time of about 1 hour. Patent Document 2 states that the high temperature antioxidant of Patent Document 2 is composed of a glass component having a softening point of 1000°C or less and having a viscosity of 10 at a temperature of 1200°C. 3 Thus, during heat treatment at high temperature, the glass composition can be maintained on the steel surface, thereby suppressing the formation of oxide scale.
[0009] Patent Document 3 envisions a heat treatment with a treatment time of about 4 hours. Patent Document 3 states: The method for preventing high-temperature oxidation of a metal material in Patent Document 3 is characterized in that, when the metal material is heated and rolled, before heating, a steel material heating antioxidant composed of 50 to 95% by weight of a glass component and 5 to 50% by weight of an aggregate is applied to a thickness of 50 to 500 μm. Thus, surface oxidation can be prevented even when heated to 900 to 1300° C. in an oxidizing atmosphere.
[0010] Patent Document 4 describes that: In Patent Document 4, an antioxidant is applied to the surface of a steel sheet, a part or all of the surface is covered with a steel plate, and the steel sheet is heated. This suppresses grain boundary oxidation.
[0011] Patent Documents 5 to 8 propose techniques for suppressing scale in alloy processed materials during annealing after hot rolling and / or cold rolling. It is believed that Patent Documents 5 to 8 envision heat treatments with a treatment time of about 1 hour. In Patent Documents 5 to 8, processed steel materials are heat treated.
[0012] Patent Document 9 states that: The method for manufacturing a seamless stainless steel pipe of Patent Document 9 is characterized in that, in a method for manufacturing a seamless stainless steel pipe in which a billet made of an iron-based alloy containing 12 wt% or more of chromium is heated to a predetermined temperature and conveyed to a subsequent rolling mill for predetermined rolling, an antioxidant is applied to the outer surface of the billet before heating, and the antioxidant is removed before rolling by the rolling mill is started. This prevents the generation of scale in the form of high-temperature oxides.
[0013] Prior art literature
[0014] Patent Literature
[0015] Patent Document 1: Japanese Patent Application Publication No. 2007-314875
[0016] Patent Document 2: Japanese Patent Application Laid-Open No. 2-209420
[0017] Patent Document 3: Japanese Patent Application Laid-Open No. 3-291325
[0018] Patent Document 4: Japanese Patent Application Laid-Open No. 56-026603
[0019] Patent Document 5: Japanese Patent Application Laid-Open No. 4-072019
[0020] Patent Document 6: Japanese Patent Application Laid-Open No. 4-072011
[0021] Patent Document 7: Japanese Patent Application Laid-Open No. 6-158153
[0022] Patent Document 8: Japanese Patent Application Laid-Open No. 7-062429
[0023] Patent Document 9: Japanese Patent Application Laid-Open No. 6-198310 Summary of the invention
[0024] Problem that the invention aims to solve
[0025] However, when heating the alloy material, a batch type heating furnace is sometimes used. In the batch type heating furnace, the alloy material is heated in a state of being stacked up and down. After the heating is completed, the alloy materials are taken out one by one from the heating furnace using a handling means such as a crane. Specifically, the top plate of the heating furnace is opened. In addition, a handling means such as a crane is used to control the alloy material arranged at the top among the multiple alloy materials stacked in the heating furnace, and the controlled alloy material is lifted from the heating furnace and taken out from the heating furnace. The taken out alloy material is arranged on a conveying path connected to a hot working device such as a rolling device.
[0026] If a plurality of alloys are exposed to a high temperature environment in a batch-type heating furnace in a state of being stacked up and down, the alloy materials stacked up and down are sometimes bonded to each other due to the antioxidant on the surface. If the alloy materials are bonded to each other, it is sometimes difficult to take the alloy material out of the heating furnace in the form of a monomer. In this specification, the degree of bonding the alloy materials to each other to the extent that it is difficult to take out from the heating furnace in the form of a monomer is called adhesion. If adhesion occurs, the operation of taking out the alloy material from the heating furnace becomes obviously complicated, and the operability is significantly reduced. Therefore, excellent adhesion resistance is required for antioxidants.
[0027] However, there is no description on the adhesion of alloy materials in Patent Documents 1 to 9. In other words, there is no study on the adhesion in Patent Documents 1 to 9.
[0028] In addition, on the other hand, alloy materials contain a large amount of alloy elements. Therefore, segregation is likely to occur in alloy materials. If heating is performed at high temperature for a long time, the diffusion of alloy elements is aggravated and segregation is reduced. Therefore, alloy materials are sometimes heated at high temperature for a long time. Specifically, before hot working, soaking is sometimes performed at a temperature of 1000 to 1350° C. for 15 to 50 hours, especially for more than 25 hours.
[0029] However, when the alloy material is soaked at a temperature of 1000 to 1350°C for a long time, such as soaking for 15 to 50 hours, excessive oxide scale will be generated on the surface of the alloy material. Excessive oxide scale will reduce the yield of the alloy material. Therefore, it is preferred that the generation of oxide scale can be suppressed even when the alloy material is soaked at a high temperature for a long time. Therefore, it is required that the antioxidant has excellent oxidation resistance even when heated at a high temperature for a long time.
[0030] The main purpose of Patent Documents 1 to 9 is not to reduce the segregation of alloy materials by high temperature and long time heating (soaking). Therefore, when the antioxidants disclosed in Patent Documents 1 to 9 are applied to the high temperature and long time heating (soaking) of the above alloy materials, the generation of oxide scale may not be fully suppressed.
[0031] The object of the present invention is to provide an antioxidant for heating an alloy material which has excellent anti-sticking properties and excellent oxidation resistance even when heated at high temperature for a long time, and a heating method for an alloy material which can inhibit sticking and further inhibit oxidation of the alloy material even when heated at high temperature for a long time.
[0032] Solutions for solving problems
[0033] The antioxidant for heating the alloy material of the present application contains, in terms of mass %,
[0034] SiO2: 40.0~80.0%,
[0035] Al2O3: 0~30.0%,
[0036] MgO: 0-5.0%,
[0037] One or more selected from the group consisting of Na2O: 10.0% or less, K2O: 20.00% or less, and CaO: 25.0% or less in an amount of 10.00 to 50.00% in total, and
[0038] B2O3: 0% or more and less than 0.5%,
[0039] The remainder consists of impurities and satisfies equation (1).
[0040] (2SiO2+Al2O3) / (0.1MgO+0.2B2O3+6Na2O+1.4K2O+2CaO)≤2.50 (1)
[0041] Here, the content of the corresponding component in mass % is substituted into each chemical formula in formula (1).
[0042] The method for heating the alloy material of the present application has the following features:
[0043] A step of applying the above-mentioned alloy material heating antioxidant to the surface of the alloy material; and
[0044] A step of heating the alloy material coated with the alloy material heating antioxidant.
[0045] Effects of the Invention
[0046] The alloy material heating antioxidant of the present application has excellent anti-adhesion property, and further, even when heated at high temperature for a long time, the oxidation resistance is also excellent. In addition, the heating method of the alloy material of the present application can suppress adhesion, and further, even when heated at high temperature for a long time, the oxidation of the alloy material can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is a plan view of a plate-shaped test piece of test number 1-1 in the examples.
[0048] Figure 2 This is a plan view of a plate-shaped test piece of Test No. 1-2 in Examples.
[0049] Figure 3 This is a plan view of a plate-shaped test piece of test number 1-3 in the example.
[0050] Figure 4 This is a cross-sectional observation diagram of Test No. 1-1 in Examples using a scanning electron microscope (Scanning Electron Microscope: SEM).
[0051] Figure 5 This is a cross-sectional observation diagram of Test No. 1-2 in the example by SEM.
[0052] Figure 6 This is a cross-sectional observation diagram of Test No. 1-3 in the example by SEM.
[0053] Figure 7 This is a diagram obtained by analyzing the cross section of the plate-shaped test piece of Test No. 1-1 in the example using an electron probe micro analyzer (EPMA).
[0054] Figure 8 This is a diagram obtained by analyzing the cross section of the plate-shaped test piece of Test No. 1-2 in the example using EPMA.
[0055] Fig. 9 This is a diagram obtained by analyzing the cross section of the plate-shaped test piece of Test No. 1-3 in the example using EPMA.
[0056] Fig.10 The amount of coal ash generated when the antioxidants for heating the alloy materials of Test No. 1-1 and Test No. 1-2 in the examples were used (mg / m 3 )’s picture.
[0057] Fig.11 is a schematic diagram of an apparatus for evaluating blocking resistance. DETAILED DESCRIPTION
[0058] The present inventors have conducted various investigations and studies on antioxidants for heating alloy materials that have excellent anti-seizing properties and excellent oxidation resistance even when heated at high temperatures for long periods of time. In the following description, heating at a temperature of 1000 to 1350° C. for 15 to 50 hours is referred to as "high temperature and long period heating".
[0059] The present inventors first investigated the reason why sufficient oxidation resistance may not be obtained when heating is performed at high temperature for a long time even when the antioxidants disclosed in Patent Documents 1 to 9 are used.
[0060] As described above, when the alloy material is heated at high temperature for a long time, it is easy to generate an oxide scale with Fe as the main component instead of the Cr2O3 film. Compared with short-term heating, especially in long-term heating of more than 15 hours, the total amount of oxygen supplied to the surface of the heated alloy material becomes more. In this case, the amount of Cr supplied from the inside of the alloy material to the surface of the alloy material is insufficient compared with the amount of Cr required for maintaining and generating the Cr2O3 film. If the amount of Cr supplied to the surface of the alloy material is insufficient, Fe is oxidized to form FeO on the surface of the alloy material before Cr. The formed FeO further reacts with the Cr2O3 film to form FeO+Cr2O3=FeCr2O4. Due to this reaction, Cr2O3 is consumed and the Cr2O3 film is damaged. In the part where the Cr2O3 film is damaged, the oxidation of the alloy material is further accelerated. As a result, an oxide scale with FeO and FeCr2O4 as the main components is generated on the surface of the alloy material. The generation of an oxide scale with FeO and FeCr2O4 as the main components is called abnormal oxidation. When abnormal oxidation occurs, the yield may decrease. Therefore, it is preferable to suppress the occurrence of abnormal oxidation during high-temperature and long-term heating.
[0061] Therefore, the inventors studied antioxidants that can inhibit abnormal oxidation. The inventors first applied high temperature and long-term heating to alloy materials coated with conventional antioxidants. As a result, it was found that in the process of high temperature and long-term heating, the antioxidants flowed or dripped from the surface of the alloy material downward. The alloy material to be heated is not only composed of a plane parallel to the horizontal plane, but is a three-dimensional shape with an upper surface, a lower surface, a side surface, etc. In the case of high temperature and long-term heating, the antioxidant softens during long-term heating and drips from the surface of the alloy material. In particular, the antioxidants applied to the side and lower surface of the alloy material in the furnace are prone to dripping downward during long-term heating. The Cr2O3 coating is easily damaged in the portion of the alloy material surface where the antioxidant drips when heated, and abnormal oxidation is prone to occur.
[0062] Therefore, the inventors of the present invention have studied antioxidants that are not easy to drip from the surface of the alloy material during high temperature and long time heating, in other words, antioxidants that are easy to remain on the surface of the alloy material even during high temperature and long time heating. As a result of the study, the inventors of the present invention considered increasing the softening point of the alloy antioxidant in order to make the alloy antioxidant remain on the surface of the alloy material. The inventors of the present invention have repeatedly conducted various studies, and the results show that if the softening point of the alloy material heating antioxidant is above 800°C, even if high temperature and long time heating is implemented, the alloy material heating antioxidant is not easy to drip from the surface of the alloy material, and the alloy material heating antioxidant is easy to remain on the surface of the alloy material. Therefore, the inventors of the present invention have studied the composition of the alloy material heating antioxidant that can make the softening point above 800°C, and obtained the alloy material heating antioxidant with a softening point of above 800°C.
[0063] However, even if an antioxidant for heating alloy materials having a softening point of 800°C or more is used, abnormal oxidation may still occur. Therefore, the inventors of the present invention have further conducted investigations and studies. As a result, it is known that even if the softening point is high, abnormal oxidation may occur when the antioxidant for heating alloy materials contains a component that reacts with the Cr2O3 film. If the antioxidant for heating alloy materials contains a component that reacts with the Cr2O3 film, the antioxidant for heating alloy materials reacts with the Cr2O3 film, and the Cr2O3 film dissolves. Therefore, in order to suppress abnormal oxidation on the surface of the alloy material, it is effective to form an antioxidant for heating alloy materials from a compound that is not easy to react with the Cr2O3 film.
[0064] As an antioxidant for heating alloy materials, glass frit is generally used. Glass frit refers to glass obtained by crushing glass into a flaky, granular or powdered form in an appropriate size. As glass frit, B2O3 is generally used. However, B2O3 reacts with the Cr2O3 film and dissolves the Cr2O3 film. Therefore, in the antioxidant for heating alloy materials of this embodiment, it is preferred to reduce the content of B2O3 as much as possible.
[0065] In addition, Na2O is also generally used as a glass frit for an antioxidant for heating alloy materials. However, Na2O also reacts with the Cr2O3 film like B2O3 to dissolve the Cr2O3 film. Therefore, in the antioxidant for heating alloy materials of this embodiment, it is also preferred to reduce the content of Na2O as much as possible.
[0066] Therefore, the inventors studied the composition of an antioxidant that suppresses the content of B2O3 and Na2O that easily react with the Cr2O3 film during high-temperature and long-term heating, and makes the softening point reach 800°C or more. As a result, it was found that if an antioxidant for heating an alloy material contains SiO2: 40.0-80.0%, Al2O3: 0-30.0%, MgO: 0-5.0% by mass% when converted into oxides, and further contains 10.00-50.00% of one or more selected from the group consisting of Na2O: 10.0% or less, K2O: 20.00% or less, and CaO: 25.0% or less, and further contains B2O3: 0% or more and less than 0.5%, it is not easy to drip from the surface of the alloy material even during high-temperature and long-term heating, and it is easy to remain on the surface of the alloy material, and it is also possible to suppress the occurrence of abnormal oxidation caused by the reaction with Cr2O3. By using the antioxidant for heating an alloy material having the above-mentioned composition and softening point, oxidation of the alloy material can be sufficiently suppressed when the alloy material is heated at a high temperature for a long time.
[0067] However, the antioxidant for heating the alloy material having the above composition and softening point may not be able to suppress the above adhesion even if it can suppress the oxidation of the alloy material during high-temperature and long-term heating. The present inventors have conducted a detailed investigation on the cause. As a result, the following insights were obtained.
[0068] The antioxidant for heating the alloy material is, for example, in the form of flakes, granules or powders before heating. The antioxidant for heating the alloy material is melted by heating. A grid structure is formed in the molten antioxidant for heating the alloy material. The grid structure is a structure that expands into a mesh in the molten antioxidant for heating the alloy material, and that can be connected to each other. The wire drawing property of the molten antioxidant for heating the alloy material is improved because the grid structure is connected to each other. Wire drawing property refers to the property of extending into a wire shape. If the wire drawing property of the antioxidant for heating the alloy material is high, the antioxidant for heating the alloy material is easily extended into a wire shape.
[0069] As described above, a batch type heating furnace is sometimes used as a heating furnace for heating the alloy material. When the alloy material is heated by a batch type heating furnace, the alloy material is heated in a stacked state in the batch type heating furnace. In the heating furnace, the alloy material is stacked with other alloy materials in a state where an antioxidant is attached to the surface. Therefore, an antioxidant is sandwiched between the stacked alloy materials. If the antioxidant has high wire drawing properties, the alloy materials stacked on each other will adhere to each other under a high temperature environment with the help of the antioxidant. If the alloy materials stacked on each other are excessively bonded, it is difficult to remove them from the heating furnace in the form of a single body. In this specification, bonding the alloy materials to each other to the extent that it is difficult to remove them from the heating furnace in the form of a single body is called adhesion. On the other hand, if the antioxidant used for heating the alloy material has low wire drawing properties, the alloy materials are not easy to adhere to each other. In this case, adhesion is suppressed.
[0070] Therefore, the present inventors have further studied from the viewpoint of composition an antioxidant having a composition that is not easily reactive with Cr2O3 and a softening point of 800°C or higher, and further capable of inhibiting adhesion. As a result, the present inventors have further obtained the following findings.
[0071] The components that form a grid structure in the coating are SiO2 and Al2O3. On the other hand, the components that cut the grid structure are MgO, B2O3, Na2O, K2O and CaO. The components that form the grid structure improve the wire drawing properties of the antioxidant for heating the alloy material. On the other hand, the components that cut the grid structure reduce the wire drawing properties of the antioxidant for heating the alloy material. Therefore, the inventors of the present invention believe that by appropriately adjusting the balance between the components that form the grid structure and the components that cut the grid structure, the wire drawing properties of the antioxidant for heating the alloy material can be reduced.
[0072] Specifically, if the antioxidant for heating the alloy material satisfies the formula (1), the wire drawing property can be reduced.
[0073] (2SiO2+Al2O3) / (0.1MgO+0.2B2O3+6Na2O+1.4K2O+2CaO)≤2.50 (1)
[0074] Here, the content of the corresponding component in mass % is substituted into each chemical formula in formula (1).
[0075] Definition: (2SiO2+Al2O3) / (0.1MgO+0.2B2O3+6Na2O+1.4K2O+2CaO)=F1. F1 can be used as an indicator of the wire drawing property of the antioxidant for heating the alloy material. If F1≤2.50, the components that cut the grid structure are sufficiently contained relative to the components that form the grid structure. In this case, the wire drawing property of the antioxidant for heating the alloy material becomes low. As a result, adhesion can be suppressed.
[0076] The antioxidant for heating an alloy material and the method for heating an alloy material according to the present embodiment, which have been completed based on the above findings, have the following configurations.
[0077] [1] An antioxidant for heating an alloy material, which contains, in terms of mass %,
[0078] SiO2: 40.0~80.0%,
[0079] Al2O3: 0~30.0%,
[0080] MgO: 0-5.0%,
[0081] One or more selected from the group consisting of Na2O: 10.0% or less, K2O: 20.00% or less, and CaO: 25.0% or less in an amount of 10.00 to 50.00% in total, and
[0082] B2O3: 0% or more and less than 0.5%,
[0083] The remainder consists of impurities and satisfies equation (1).
[0084] (2SiO2+Al2O3) / (0.1MgO+0.2B2O3+6Na2O+1.4K2O+2CaO)≤2.50 (1)
[0085] Here, the content of the corresponding component in mass % is substituted into each chemical formula in formula (1).
[0086] [2] A method for heating an alloy material, comprising:
[0087] A step of applying the alloy material heating antioxidant described in [1] to the surface of the alloy material; and
[0088] A step of heating the alloy material coated with the alloy material heating antioxidant.
[0089] [3] The method for heating an alloy material according to [2], wherein:
[0090] The chemical composition of the alloy material contains 12 to 50 mass % of Cr.
[0091] [4] The method for heating an alloy material according to [3], wherein:
[0092] The chemical composition of the alloy material contains 1 to 15 mass % of Mo.
[0093] [5] The method for heating an alloy material according to any one of [2] to [4], wherein:
[0094] In the heating step, the alloy material coated with the alloy material heating antioxidant is heated at a temperature of 1000 to 1350° C. for 15 to 50 hours.
[0095] The antioxidant for heating the alloy material described in this embodiment is suitable for heating the alloy material to form a Cr2O3 coating at a temperature of 1000-1350°C for 15-50 hours, and is particularly suitable for heating at a high temperature of more than 1300°C for more than 25 hours.
[0096] If the alloy material heating antioxidant of this embodiment is used, the alloy material to form a Cr2O3 film has excellent oxidation resistance even if it is heated for a long time at 1000 to 1350°C for 15 to 50 hours. The alloy material heating antioxidant of this embodiment also has excellent anti-seizing property.
[0097] The antioxidant for heating alloy materials according to this embodiment is described in detail below. Unless otherwise specified, "%" related to each component means mass % when the total amount of the compound composition of the antioxidant for heating alloy materials is 100%.
[0098] The antioxidant for heating the alloy material of the present embodiment contains the following compounds. If the antioxidant for heating the alloy material is composed of the following compounds, the softening point of the antioxidant for heating the alloy material can be made above 800°C. It should be noted that the antioxidant for heating the alloy material is a glass material in the form of flakes, particles or powders, and the content of each compound is the average content contained in one glass material.
[0099] SiO2: 40.0~80.0%
[0100] Silicon dioxide (SiO2) forms a protective film on the surface of the alloy material together with other components during high temperature and long time heating. SiO2 becomes the matrix of the protective film. The protective film inhibits the supply of oxygen to the surface of the alloy material. SiO2 also has a high softening point of more than 1600°C. If the antioxidant for heating the alloy material contains SiO2, the softening point of the antioxidant for heating the alloy material is improved. Therefore, during high temperature and long time heating, the antioxidant for heating the alloy material is not easy to drip from the surface of the alloy material and is easy to remain on the surface of the alloy material. If the SiO2 content in the antioxidant for heating the alloy material is more than 40.0%, the surface of the alloy material can be covered even during high temperature and long time heating, inhibiting the supply of oxygen to the surface of the alloy material. As a result, the oxidation resistance is improved. If the oxidation resistance is high, when using an alloy material that also contains Mo, the coal ash from MoO3 can be suppressed. That is, the dust resistance is improved. When the SiO2 content is less than 40.0%, the viscosity of the antioxidant for heating the alloy material becomes low during high temperature and long time heating, and it is easy to drip. As a result, the above-mentioned effects cannot be fully obtained. On the other hand, if the SiO2 content exceeds 80.0%, the softening point of the antioxidant for heating the alloy material becomes too high. In this case, the antioxidant for heating the alloy material is not easy to wet and spread. As a result, it is difficult to uniformly cover the entire surface of the alloy material with the antioxidant for heating the alloy material, and the oxidation resistance is reduced. If the oxidation resistance is reduced, the dust resistance is also reduced when using an alloy material containing Mo. If the SiO2 content exceeds 80.0%, the softening point of the antioxidant for heating the alloy material becomes further higher. Therefore, the mixed components are not easy to melt, and the manufacture of the antioxidant for heating the alloy material itself becomes difficult. Therefore, the SiO2 content is 40.0 to 80.0%. The lower limit of the SiO2 content is preferably 45.0%, and more preferably 50.0%. The upper limit of the SiO2 content is preferably 75.0%, and more preferably 70.0%.
[0101] Al2O3: 0~30.0%
[0102] Aluminum oxide (Al2O3) may not be contained. In other words, the Al2O3 content may be 0%. When contained, Al2O3 forms a protective film on the surface of the alloy material during high-temperature and long-term heating, similarly to SiO2. Al2O3 further increases the softening point of the antioxidant for heating the alloy material. Therefore, during high-temperature and long-term heating, the antioxidant for heating the alloy material is not easy to drip and is likely to remain on the surface of the alloy material. As a result, the oxidation resistance of the alloy material is improved. If the oxidation resistance of the alloy material is improved, the dustproofness is also improved when an alloy material containing Mo is used. However, if the Al2O3 content exceeds 30.0%, the content ratio of SiO2 will decrease, and therefore, the protective film will not form a matrix of the SiO2 main body. As a result, the viscosity of the antioxidant for heating the alloy material becomes low, and dripping occurs during high-temperature and long-term heating. Therefore, the Al2O3 content is 0 to 30.0%. The lower limit of the Al2O3 content is preferably 1.0%, more preferably 5.0%, and more preferably 10.0%. The upper limit of the Al2O3 content is preferably 28.0%, more preferably 25.0%.
[0103] MgO: 0~5.0%
[0104] Magnesium oxide (MgO) may not be contained. In other words, the MgO content may be 0%. When contained, MgO forms a protective film on the surface of the alloy material during high-temperature and long-term heating, similar to SiO2 and Al2O3. MgO further reduces the softening point of the antioxidant used for heating the alloy material. Therefore, during high-temperature and long-term heating, the antioxidant used for heating the alloy material wets and diffuses, uniformly covering the surface of the alloy material. However, if the MgO content exceeds 5.0%, MgO will dissolve the Cr2O3 film as a protective film, so the Cr2O3 film will not be fully formed. As a result, oxidation resistance is reduced. In addition, when an alloy material containing Mo is used, dust resistance is also reduced. Therefore, the MgO content is 0 to 5.0%. The lower limit of the MgO content is preferably 0.1%, and more preferably 0.2%. The upper limit of the MgO content is preferably 4.0%, and more preferably 3.0%.
[0105] One or more selected from the group consisting of Na2O: 10.0% or less, K2O: 20.00% or less, and CaO: 25.0% or less: 10.00 to 50.00% in total
[0106] Na2O exceeds 0%, K2O exceeds 0%, and CaO exceeds 0%. When the total content of one or more selected from the group consisting of Na2O: 10.0% or less, K2O: 20.00% or less, and CaO: 25.0% or less is less than 10.00%, the fluidity of the antioxidant for heating the alloy material at high temperature decreases. On the other hand, when the total content of one or more selected from the group consisting of Na2O: 10.0% or less, K2O: 20.00% or less, and CaO: 25.0% or less exceeds 50.00%, the softening point of the antioxidant for heating the alloy material will be excessively reduced. If the softening point of the antioxidant for heating the alloy material is reduced, the antioxidant for heating the alloy material will drip from the surface of the alloy material during high-temperature and long-term heating. Therefore, the total content of one or more selected from the group consisting of Na2O: 10.0% or less, K2O: 20.00% or less, and CaO: 25.0% or less is 10.00-50.00%.
[0107] The lower limit of the total content of one or more selected from the group consisting of Na2O: 10.0% or less, K2O: 20.00% or less, and CaO: 25.0% or less is preferably 15.00%, and more preferably 20.00%. The upper limit of the total content of one or more selected from the group consisting of Na2O: 10.0% or less, K2O: 20.00% or less, and CaO: 25.0% or less is preferably 45.00%, and more preferably 40.00%.
[0108] Na2O: 10.0% or less
[0109] Sodium oxide (Na2O) is inevitably contained in the antioxidant for heating alloy materials mainly composed of SiO2. Na2O will increase the fluidity of the antioxidant for heating alloy materials at high temperatures. However, Na2O easily reacts with the Cr2O3 coating and damages the Cr2O3 coating. In particular, when the Cr content of the alloy material is less than 20.0 mass%, the Cr2O3 coating is easily damaged. Furthermore, if the Na2O content exceeds 10.0%, the softening point of the antioxidant for heating the alloy material is excessively reduced. Therefore, the Na2O content is less than 10.0%, and more specifically, the Na2O content exceeds 0% and is less than 10.0%. The lower limit of Na2O is preferably 0.1%, and more preferably 0.2%. The upper limit of the Na2O content is preferably 9.0%, more preferably 7.0%, more preferably 6.0%, more preferably 5.0%, more preferably 4.0%, more preferably 3.0%, and more preferably 2.0%.
[0110] K2O: 20.00% or less
[0111] Potassium oxide (K2O) is inevitably contained in the antioxidant for heating alloy materials mainly composed of SiO2. K2O will reduce the softening point of the antioxidant for heating alloy materials. If the softening point is reduced, the fluidity at high temperature is improved, and it is easy to wet and diffuse to the surface of the alloy material. As a result, it is easy to evenly cover the surface of the alloy material with the antioxidant for heating alloy materials. However, if the K2O content exceeds 20.00%, the softening point of the antioxidant for heating alloy materials is excessively reduced. In this case, during high-temperature and long-term heating, the antioxidant for heating alloy materials drips from the surface of the alloy material, and abnormal oxidation is likely to occur. If the antioxidant for heating alloy materials drips from the surface of the alloy material, when using an alloy material containing Mo, coal ash derived from MoO3 is likely to be generated. Therefore, the K2O content is less than 20.00%, and more specifically, the K2O content exceeds 0% and is less than 20.00%. The lower limit of the K2O content is preferably 0.01%, and more preferably 0.02%. The upper limit of the K2O content is preferably 19.50%, more preferably 19.00%.
[0112] CaO: 25.0% or less
[0113] Calcium oxide (CaO) is inevitably contained in the antioxidant for heating alloy materials mainly composed of SiO2. CaO, like K2O, will reduce the softening point of the antioxidant for heating alloy materials. If the softening point decreases, the fluidity at high temperature increases, and it is easy to wet and diffuse to the surface of the alloy material. As a result, it is easy to evenly cover the surface of the alloy material with the antioxidant for heating alloy materials. However, if the CaO content exceeds 25.0%, the softening point of the antioxidant for heating alloy materials is excessively reduced. If the softening point of the antioxidant for heating alloy materials is reduced, the antioxidant for heating alloy materials drips from the surface of the alloy material during high temperature and long-term heating, and abnormal oxidation is likely to occur. If the antioxidant for heating alloy materials drips from the surface of the alloy material, when using an alloy material containing Mo, coal ash derived from MoO3 is likely to be generated. Therefore, the CaO content is less than 25.0%, and more specifically, the CaO content exceeds 0% and is less than 25.0%. The lower limit of the CaO content is preferably 0.6%, more preferably 0.8%, more preferably 10.0%, more preferably 11.0%, and more preferably 12.0%. The upper limit of the CaO content is preferably 24.5%, and more preferably 24.0%.
[0114] B2O3: 0% or more and less than 0.5%
[0115] Boric acid (B2O3) is an impurity. In other words, the B2O3 content can be 0%. B2O3 is a compound known as an antioxidant. However, B2O3 reacts with the Cr2O3 film and dissolves the Cr2O3 film during high-temperature and long-term heating. In this case, abnormal oxidation is likely to occur. If the Cr2O3 film is dissolved, when an alloy material that also contains Mo is used, coal ash derived from MoO3 is likely to be produced. Therefore, the B2O3 content is greater than 0% and less than 0.5%. The B2O3 content is preferably as low as possible. The upper limit of the B2O3 content is preferably 0.4%, more preferably 0.3%, and more preferably 0%.
[0116] The remainder of the compound composition of the antioxidant for heating alloy materials according to the embodiment of the present invention is composed of impurities. Here, impurities refer to substances mixed from inorganic materials as raw materials or manufacturing environment when the antioxidant for heating alloy materials is manufactured industrially, and are acceptable within the range of not causing adverse effects on the antioxidant for heating alloy materials of the present embodiment.
[0117] [Formula (1)]
[0118] The antioxidant for heating the alloy material satisfies the formula (1).
[0119] (2SiO2+Al2O3) / (0.1MgO+0.2B2O3+6Na2O+1.4K2O+2CaO)≤2.50 (1)
[0120] Here, the content of the corresponding component in mass % is substituted into each chemical formula in formula (1).
[0121] Definition: (2SiO2+Al2O3) / (0.1MgO+0.2B2O3+6Na2O+1.4K2O+2CaO)=F1. If F1 exceeds 2.50, the components of the antioxidant for heating the alloy material contain excessive components that form the grid structure compared to the components that cut the grid structure. Therefore, the wire drawing property of the antioxidant for heating the alloy material is improved. As a result, after being heated at high temperature for a long time, the alloy materials adhere to each other and stick together. Therefore, F1≤2.50. The upper limit of F1 is preferably 2.45, more preferably 2.40, and more preferably 2.30. The lower limit of F1 is not particularly limited, for example, it is 0.62.
[0122] [Softening point]
[0123] The softening point of the antioxidant for heating the alloy material is above 800°C. If the softening point of the antioxidant for heating the alloy material is above 800°C, when high temperature and long time heating is implemented, the antioxidant for heating the alloy material wets and diffuses to the entire surface of the alloy material and covers the surface. As a result, the oxidation of the surface of the alloy material can be suppressed. When the softening point of the antioxidant for heating the alloy material is lower than 800°C, when high temperature and long time heating is implemented, the antioxidant for heating the alloy material drips from the surface of the alloy material, and the surface of the alloy material is partially exposed. In the exposed part, the supply of oxygen to the surface of the alloy material cannot be suppressed. As a result, abnormal oxidation occurs on the surface of the alloy material. Furthermore, since the supply of oxygen to the surface of the alloy material cannot be suppressed, when an alloy material containing Mo is used, coal ash derived from MoO3 is easily generated. Therefore, the softening point of the antioxidant for heating the alloy material is above 800°C. The lower limit of the softening point of the antioxidant for heating the alloy material is preferably 820°C, more preferably 840°C, and more preferably 860°C. The upper limit of the softening point of the antioxidant for heating the alloy material is not particularly limited, but is, for example, 1100°C.
[0124] The softening point of the antioxidant for heating the alloy material is determined by the composition of the compound of the antioxidant for heating the alloy material. If the composition of the compound of the antioxidant for heating the alloy material is the present embodiment, the softening point reaches 800°C or more.
[0125] [Measurement method of softening point]
[0126] The softening point of the antioxidant for heating the alloy material is measured using a thermogravimetric-differential thermal simultaneous determination device (TG-DTA). The details are as follows. Place 10 mg of the antioxidant for heating the alloy material on the sample holder of the TG-DTA. Heat the antioxidant for heating the alloy material to 1300°C at a heating rate of 10°C / min. The atmosphere during heating is set to air. Measure the differential thermal at this time, and take the fourth inflection point of the DTA (differential thermal) spectrum as the softening point of the antioxidant for heating the alloy material.
[0127] The antioxidant for heating alloy materials has excellent anti-seizing property and also excellent oxidation resistance even when heated at high temperature for a long time. The present inventors have further found that the antioxidant for heating alloy materials exhibits excellent dustproof property when applied to alloy materials containing Mo.
[0128] When using a conventional antioxidant for heating alloy materials containing SiO2 and more than 10.0% of Na2O, as described above, Na2O will excessively dissolve the Cr2O3 film of the alloy material. If the Cr2O3 film is dissolved, the Mo inside the alloy material reacts with oxygen in the air to generate MoO3. MoO3 has a low boiling point. Therefore, during high-temperature, long-term heating and hot working, white coal ash originating from MoO3 is generated. Coal ash reduces the observability of operators. Therefore, it is preferred to be able to suppress the generation of coal ash originating from MoO3.
[0129] When the alloy material heating antioxidant of the present embodiment is used, the Cr2O3 coating is not easily dissolved. Therefore, the Mo inside the alloy material is not easily oxidized and is not easily generated as MoO3. As a result, the generation of white coal ash originating from MoO3 can be suppressed during high-temperature, long-term heating and hot working.
[0130] [Form of antioxidant for heating alloy materials]
[0131] The antioxidant for heating the alloy material is glass frit. Glass frit refers to glass obtained by melting and solidifying the powders of the above-mentioned components and then pulverizing them. The antioxidant for heating the alloy material is in the form of flakes, particles or powder, for example.
[0132] When the antioxidant for heating the alloy material is in powder form, the particle size is preferably less than 25 μm. The particle size mentioned here is the volume average particle size (median particle size) D50. The volume average particle size D50 is obtained by the following method. The volume particle size distribution of the glass material is obtained using a particle size distribution measuring device. Using the obtained volume particle size distribution, the particle size when the cumulative volume from the small particle size side in the cumulative volume distribution reaches 50% is defined as the volume average particle size D50. If the particle size is less than 25 μm, the antioxidant for heating the alloy material is easily dispersed in the solution (water) at room temperature, and slurry is easily generated.
[0133] [Method for producing antioxidant for heating alloy materials]
[0134] The antioxidant for heating alloy materials of the present embodiment is manufactured by the following method. The above-mentioned components constituting the antioxidant for heating alloy materials are mixed. The mixed components are melted and quenched in water or air to vitrify them. The melting temperature is, for example, 1400 to 1600°C. After melting, the components are quenched and crushed. The particle size of the antioxidant for heating alloy materials of the present embodiment is, for example, 1μm to 25μm. Thereby, the softening point of the antioxidant for heating alloy materials of the present embodiment can be adjusted. The antioxidant for heating alloy materials of the present embodiment is manufactured by the above process.
[0135] The antioxidant for heating alloy materials of the present embodiment can be used to manufacture alloy materials. The antioxidant for heating alloy materials of the present embodiment can be applied when, for example, an alloy material having a Cr content of 12 to 50% by mass is heated for 15 to 50 hours at a temperature of 1000 to 1350°C (high temperature and long time heating). The antioxidant for heating alloy materials of the present embodiment is particularly suitable for heating at a temperature of 1300°C or above and for more than 25 hours. Even in the case of short-term heating of less than 15 hours at a temperature of 1000 to 1350°C, it has excellent oxidation resistance. This point is explained below.
[0136] [Alloy material]
[0137] The alloy material for which the alloy material heating antioxidant of the present embodiment is used refers to an Fe-based or Ni-based alloy material containing Cr. The Fe-based alloy material refers to an alloy material having an Fe content of 50% by mass or more. The Ni-based alloy material refers to an alloy material having an Ni content of 50% by mass or more. The Cr content in the alloy material may be 12 to 50% by mass. The Cr content in the alloy material may be 20 to 40% by mass. The alloy material containing Cr may be, for example, an alloy material containing Si: 0 to 5%, Mn: 0 to 20%, Cr: 12 to 50%, Mo: 0 to 15%, W: 0 to 10%, Cu: 0 to 5%, Ti: 0 to 3%, V: 0 to 1%, Al: 0 to 5%, and the total content of the above elements and Fe and / or Ni is 99% or more. If the Cr content of the alloy material is 20% by mass or more, it is easy to maintain the Cr2O3 coating for a longer period of time.
[0138] The antioxidant for heating the alloy material of the present embodiment is particularly suitable for the alloy material of the casting material. The alloy material is, for example, a stainless steel material, such as a martensitic stainless steel material, a ferritic stainless steel material, an austenitic stainless steel material, a precipitation solidification stainless steel material, and a duplex stainless steel material. The antioxidant for heating the alloy material of the present embodiment is particularly suitable for the alloy material of the casting material. However, the antioxidant for heating the alloy material of the present embodiment is not limited to the casting material, and can be applied to the processed material obtained by hot working the casting material. In short, the antioxidant for heating the alloy material of the present embodiment can be widely used in alloy materials (casting materials, processed materials).
[0139] Furthermore, when the antioxidant for heating alloy materials of the present embodiment uses an alloy material belonging to the above alloy material and having a Mo content exceeding 0%, it has excellent dust resistance. As described above, when heated at high temperature for a long time, the Cr2O3 film is easily dissolved. If the Cr2O3 film of the alloy material containing Mo is dissolved, MoO3 is generated. As a result, coal ash derived from MoO3 is generated. However, when the antioxidant for heating alloy materials of the present embodiment is used, the Cr2O3 film can be maintained for a longer time, and therefore, the generation of MoO3 can be suppressed.
[0140] [Method for heating alloy material using the antioxidant for heating alloy material according to the present embodiment]
[0141] The method for heating an alloy material according to the present embodiment includes: a step of applying an antioxidant for heating an alloy material to the surface of the alloy material; and a step of heating the alloy material coated with the antioxidant for heating an alloy material.
[0142] [Coating process]
[0143] In the coating process, first, an antioxidant for heating the alloy material is prepared. The prepared antioxidant for heating the alloy material is made into a slurry, for example. The slurry is prepared by mixing water into the antioxidant for heating the alloy material. The slurry is applied to the surface (upper surface, lower surface and side surface) of the alloy material before heating. By applying the antioxidant for heating the alloy material in the form of a slurry, it is easy to apply the antioxidant for heating the alloy material roughly uniformly on the surface of the alloy material before heating.
[0144] In the slurry, the water content is preferably 70 to 100 parts by mass relative to 100 parts by mass of the antioxidant for heating the alloy material. If the water content is too little or too much, it is difficult to apply the antioxidant for heating the alloy material. If the water content is adjusted, the viscosity of the slurry can be adjusted at room temperature to a degree that can be roughly evenly applied to the surface of the alloy material.
[0145] The slurry may further contain suspending agents and dispersing agents.
[0146] The suspending agent disperses the antioxidant for heating the alloy material and the like in a solution (water) approximately uniformly. The suspending agent contains, for example, frog clay and bentonite and / or sepiolite. If the antioxidant for heating the alloy material of the present embodiment is applied to the surface of the alloy material together with frog clay and bentonite and / or sepiolite, the antioxidant for heating the alloy material is not easy to drip on the surface of the alloy material, and when dried to form a solid, the antioxidant for heating the alloy material is not easy to peel off from the surface of the alloy material.
[0147] Frog clay contains kaolinite clay and a plurality of quartz particles. More specifically, Frog clay contains kaolinite, halloysite, and quartz.
[0148] Frog clay improves the drip resistance of the liquid antioxidant for heating alloy materials. After the slurry containing frog clay is applied to the surface of the alloy material at room temperature, it is not easy to drip. Therefore, if frog clay is contained, the antioxidant for heating alloy materials can easily cover the entire surface of the alloy material at room temperature.
[0149] In the case where the slurry contains frog eye soil, in the slurry, relative to 100 parts by mass of the alloy material heating antioxidant, the content of frog eye soil is preferably more than 4 parts by mass. In this case, the alloy material heating antioxidant at room temperature is not easy to drip. The content of frog eye soil is more preferably more than 5 parts by mass, and more preferably more than 6 parts by mass. If the slurry contains frog eye soil excessively, the alloy material heating antioxidant in the slurry is not easy to be evenly dispersed on the surface of the alloy material, and oxidation resistance is reduced. Therefore, the upper limit of the content of frog eye soil is preferably 30 parts by mass.
[0150] However, even if the content of the quartz sand is less than 4 parts by mass, the dripping of the antioxidant for heating the alloy material at room temperature can be suppressed to some extent.
[0151] Bentonite is clay containing montmorillonite as a main component and may further contain silicate minerals such as quartz and opal, silicate minerals such as feldspar and zeolite, carbonate minerals such as dolomite, sulfate minerals, sulfide minerals such as pyrite, and the like.
[0152] Sepiolite is a hydrous magnesium silicate, for example Mg8Si 12 O 30 The chemical formula of (OH)4(OH2)4·8H2O.
[0153] Both bentonite and sepiolite can inhibit the peeling of the antioxidant for heating the alloy material. Specifically, a liquid slurry is applied to the surface of the alloy material. And, by heating or drying, the water in the slurry applied to the alloy material evaporates, and the antioxidant for heating the alloy material solidifies. In the case where the slurry contains bentonite and / or sepiolite, the bentonite and sepiolite can inhibit the solidified antioxidant for heating the alloy material from peeling off from the surface of the alloy material. The slurry containing bentonite and / or sepiolite is not easy to peel off even when subjected to external force. In the case where the slurry contains bentonite and / or sepiolite, the slurry only needs to contain any one or more of bentonite and sepiolite.
[0154] In the case where the slurry contains bentonite and / or sepiolite, in the slurry, relative to 100 parts by mass of the antioxidant for heating the alloy material, the lower limit of the content of bentonite and / or sepiolite is preferably 4 parts by mass or more. If the content of bentonite and / or sepiolite is 4 parts by mass or more, the stripping resistance of the antioxidant for heating the alloy material is further improved. In the case where the slurry contains bentonite and sepiolite, the lower limit of the total value of the bentonite content and the sepiolite content is preferably 5 parts by mass or more.
[0155] In addition, when the slurry contains bentonite and / or sepiolite, the upper limit of the content of bentonite and / or sepiolite is preferably less than 9 parts by mass relative to 100 parts by mass of the antioxidant for heating the alloy material. If the content of bentonite and / or sepiolite exceeds 9 parts by mass, the antioxidant for heating the alloy material is not easy to disperse in the liquid slurry. In other words, the antioxidant for heating the alloy material is not easy to slurry. When the slurry contains bentonite and sepiolite, the upper limit of the total value of the bentonite content and the sepiolite content is preferably less than 8 parts by mass.
[0156] However, even when the content of bentonite and / or sepiolite exceeds the above range, the effect of suppressing the peeling of the antioxidant for heating the alloy material can be obtained to some extent.
[0157] The suspending agent may contain clays other than the above-mentioned terra alba, bentonite and sepiolite. Clays contain, for example, iron oxide (Fe2O3).
[0158] In the embodiment of the present invention, the slurry may not contain a dispersant. However, from the viewpoint of improving the overall dispersibility of the antioxidant for heating the alloy material and improving the workability, the slurry preferably contains a dispersant. If the slurry contains a dispersant, the amount of water for dispersing the antioxidant for heating the alloy material can be further reduced, and as a result, the adhesion is improved. The dispersant is, for example, selected from one or more of the group consisting of inorganic salts such as sodium tripolyphosphate, sodium hexametaphosphate, sodium polyphosphate, acid sodium hexametaphosphate, sodium borate, sodium carbonate, polymetaphosphoric acid, sodium citrate, sodium tartrate, polyacrylic acid, sodium polyacrylate, sodium sulfonate, polycarboxylate, β-naphthalenesulfonate, melanin sulfonate and naphthalenesulfonic acid. In the slurry, the total content of the dispersant is preferably less than 4.5 parts by mass relative to 100 parts by mass of the antioxidant for heating the alloy material.
[0159] The slurry of the alloy material heating antioxidant is applied to the surface of the alloy material before heating. In other words, the slurry of the alloy material heating antioxidant is applied to the surface of the alloy material at room temperature.
[0160] The coating method of the alloy material heating antioxidant made into slurry is not particularly limited. The operator can use a brush to apply the alloy material heating antioxidant made into slurry on the surface of the alloy material. In addition, the alloy material heating antioxidant made into slurry can also be applied to the surface of the alloy material by spraying, etc. A bathtub storing the alloy material heating antioxidant made into slurry can also be prepared, and the alloy material is immersed in the bathtub (so-called "tank immersion"). Through these coating methods, the alloy material heating antioxidant is applied to the surface of the alloy material. After the alloy material heating antioxidant is applied to the surface of the alloy material, the alloy material heating antioxidant can be dried.
[0161] [Heating process]
[0162] Next, the alloy material coated with the antioxidant for heating the alloy material is heated (heating step). In the heating step, the alloy material coated with the antioxidant for heating the alloy material is heated at a temperature of, for example, 1000 to 1350° C. for 15 to 50 hours.
[0163] The antioxidant for heating the alloy material of the present embodiment contains the above-mentioned compound. The above-mentioned compound is not easy to react with the Cr2O3 film on the surface of the alloy material. Therefore, during high-temperature and long-term heating, the Cr2O3 film is inhibited from being damaged. Furthermore, when applied to alloy materials containing Mo, coal ash from MoO3 can be inhibited. Furthermore, the softening point of the antioxidant for heating the alloy material of the present embodiment is above 800°C. Therefore, even during high-temperature and long-term heating, the antioxidant for heating the alloy material is not easy to drip from the surface of the alloy material, but remains on the surface of the alloy material. As a result, the occurrence of abnormal oxidation can be suppressed, and even if it is heated at high temperature for a long time, the oxidation of the alloy material can be suppressed. The antioxidant for heating the alloy of the present embodiment also satisfies formula (1). Therefore, the wire drawing property of the antioxidant for heating the alloy material is low. As a result, the adhesion of the alloy materials to each other can be suppressed, and adhesion can be suppressed.
[0164] [Example 1]
[0165] The following examples will more specifically describe the effects of the antioxidant for heating alloy materials of the present embodiment. The conditions in the following examples are a conditional example adopted to confirm the feasibility and effect of the antioxidant for heating alloy materials of the present embodiment. Therefore, the antioxidant for heating alloy materials of the present embodiment is not limited to this conditional example.
[0166] A plurality of antioxidants for heating alloy materials having different compound compositions were prepared, and an oxidation confirmation test and an oxidation loss measurement test were performed as an evaluation of oxidation resistance using the prepared plurality of antioxidants for heating alloy materials.
[0167] [Oxidation confirmation test]
[0168] Prepare an antioxidant for heating the alloy material shown in Table 1. Test No. 1-1 and Test No. 1-4 are the compositions described in Table 1, and the remainder is impurities. The composition of the antioxidant for heating the alloy material is obtained by drying the alloy material after manufacturing the antioxidant for heating the alloy material and performing high-frequency inductively coupled plasma (ICP: Inductively Coupled Plasma) analysis. Specifically, the contents of Si, Al, Mg, Na, K, Ca and B obtained by ICP are converted into the contents of SiO2, Al2O3, MgO, Na2O, K2O, CaO and B2O3, respectively, and the content of each component is calculated. Test No. 1-2 uses the product name AKNAS (softening point: 700°C) manufactured by Dongcan Materials Technology Co., Ltd. The composition of the compound of the product name AKNAS is unknown.
[0169] [Table 1]
[0170]
[0171] The softening point of the antioxidant for heating the alloy material of each test number was determined using a thermogravimetric-differential thermal simultaneous determination device (TG-DTA). Specifically, 10 mg of the antioxidant for heating the alloy material was placed on the sample holder of the TG-DTA. The antioxidant for heating the alloy material was heated to 1300°C at a heating rate of 10°C / min. The atmosphere during heating was set to air. The latent heat at this time was determined, and the fourth inflection point of the DTA (differential thermal) spectrum was used as the softening point of the antioxidant for heating the alloy material. The results are shown in Table 1.
[0172] A plate-shaped test piece simulating an alloy material was prepared. A duplex stainless steel material corresponding to A240UNS S39274 specified in ASTM was used as the plate-shaped test piece. The dimensions of the plate-shaped test piece were 13 mm thick, 40 mm long, and 100 mm wide.
[0173] The slurry was prepared by mixing 6 parts by mass of clay, 5 parts by mass of bentonite, and 70 to 100 parts by mass of water with 100 parts by mass of an antioxidant for heating the alloy material. The obtained slurry was applied to a 40 mm x 100 mm surface of a plate-shaped test piece using a brush and then dried.
[0174] The plate-shaped test piece coated with the alloy material heating antioxidant was heated at 1300°C for 25 hours. The atmosphere was simulated to burn LNG. Specifically, the atmosphere was adjusted to have a composition of 2-3% O2, 8-10% CO2, 15-20% H2O and the balance N2.
[0175] The following method is used to confirm whether abnormal oxidation occurs in the plate-like test piece after heating. For the plate-like test piece after heating, the 40mm×100mm surface as the upper surface is observed visually. Furthermore, a scanning electron microscope (Scanning Electron Microscope: SEM) is used to observe the surface portion of the plate-like test piece (near the 40mm×100mm surface) in the cross section perpendicular to the 40mm×100mm surface. The observation conditions of the SEM are set to: 40 times the magnification and a field of view of 2000μm×2000μm. Confirm the presence or absence of abnormal oxidation by visual inspection. According to the visual evaluation, the presence of abnormal oxidation in the 40mm×100mm surface of the plate-like test piece and / or the cross section perpendicular to the 40mm×100mm surface will be recorded as unqualified (indicated by "unqualified" in the "Oxidation Confirmation Test" "Pass or Fail" column of Table 1). The case where there was no abnormal oxidation was regarded as passing (indicated by "pass" in the "Oxidation confirmation test" column of Table 1).
[0176] Figure 1 This is a plan view of the plate-shaped test piece of test number 1-1. Figure 2 This is a plan view of the plate-shaped test piece of test number 1-2. Figure 3 This is a plan view of the plate-shaped test piece of test number 1-3. When an abnormal oxidation area is clearly observed on the upper surface of the 40 mm × 100 mm plate-shaped test piece (for example, Figure 2 The symbol 1 and Figure 3 On the other hand, if Figure 1 In this way, when abnormal oxidation is not observed in the surface of 40 mm×100 mm of the test piece, it is determined that abnormal oxidation has not occurred.
[0177] Furthermore, the influence on the base material was also investigated by SEM observation of a cross section perpendicular to a surface of 40 mm×100 mm. Figure 4 This is a cross-sectional observation picture of Test No. 1-1 by SEM. Figure 5 This is a cross-sectional observation diagram of Test No. 1-2 using SEM. Figure 6 This is a cross-sectional observation diagram of test number 1-3 based on SEM. Figure 4 If abnormal oxidation is not observed, it is determined that abnormal oxidation has not occurred. On the other hand, if an abnormal oxidation region is clearly observed in a cross section perpendicular to the 40 mm × 100 mm surface (for example, Figure 5 The symbol 3 and Figure 6 When the oxide scale as shown in symbol 4 is observed and the base material is thinned), it is judged that abnormal oxidation has occurred.
[0178] Furthermore, an elemental analysis based on elemental mapping was performed on a cross section perpendicular to the 40 mm × 100 mm surface of the plate-shaped test piece using an electron probe micro analyzer (EPMA). The state of the oxide scale was analyzed by elemental analysis. The results are shown in Figure 7 to Figure 9 . Figure 7 This is a diagram showing the element mapping analysis results of Test No. 1-1. Figure 8 This is a diagram showing the element mapping analysis results of Test No. 1-2. Fig. 9 It is a diagram showing the element mapping analysis results of test numbers 1-3.
[0179] [Test results]
[0180] Referring to Table 1, in Test No. 1-1, since the composition of the compound is appropriate, the softening point of the antioxidant for heating the alloy material is 800°C or more. Figure 1 and Figure 7 A Cr2O3 coating 2 with a uniform thickness was formed on the surface of the plate-shaped test piece, and normal oxidation was observed. Figure 4 In the test number 1-1, the base material 10 was not further reduced in thickness. In other words, the oxidation resistance of the alloy material was improved by using the antioxidant for heating the alloy material of the test number 1-1.
[0181] In test number 1-4, the composition of the compound is also appropriate, so the softening point of the antioxidant for heating the alloy material is above 800°C. As a result, a Cr2O3 film of uniform thickness is formed on the surface of the plate-shaped test piece, and normal oxidation is observed. In test number 1-4, the base material is not further thinned. In other words, by using the antioxidant for heating the alloy material of test number 1-4, the oxidation resistance of the alloy material is improved.
[0182] On the other hand, in Test No. 1-2, the softening point of the antioxidant for heating the alloy material is lower than 800°C. Since the softening point is lower than 800°C, it can be considered that the compound composition in Test No. 1-2 is also inappropriate. Figure 2 , abnormal oxidation 1 occurred. In test number 1-2, further reference is made to Figure 5 , a depression with a depth of about 1.5 mm was generated in the base material 20. In test number 1-2, further reference is made to Figure 8 , an oxide scale 3 mainly composed of Fe was formed. Since the antioxidant for heating the alloy material of Test No. 1-2 was used, the oxidation resistance of the alloy material was not improved.
[0183] In test number 1-3, no antioxidant for heating the alloy material was used. Figure 3The entire surface of the plate-shaped test piece was severely oxidized. Figure 6 The surface of the base material 30 is thinned by about 0.8 mm, and an oxide scale 4 is formed. Fig. 9 , forming an oxide scale 4 mainly composed of Fe and Cr.
[0184] [Oxidation reduction test]
[0185] Prepare the antioxidant for heating the alloy material shown in Table 2. Test numbers 2-2 to 2-4 are the compositions described in Table 2. In test number 2-2, the total amount of the components described in Table 2 is 100% by mass. In test numbers 2-3 and 2-4, the total amount of the components described in Table 2 is less than 100% by mass, and the remainder is impurities. The composition of the antioxidant for heating the alloy material is obtained by drying and performing ICP analysis after manufacturing the antioxidant for heating the alloy material. Specifically, the contents of Si, Al, Mg, Na, K, Ca and B obtained by ICP are converted into the contents of SiO2, Al2O3, MgO, Na2O, K2O, CaO and B2O3, respectively, and the content of each component is calculated.
[0186] [Table 2]
[0187]
[0188] Prepare a plate-shaped test piece simulating an alloy material. The plate-shaped test piece is a stainless steel material containing 87% Fe and 13% Cr by mass. The dimensions of the plate-shaped test piece are 10 mm thick, 20 mm long, and 20 mm wide. Measure the mass (g) of the plate-shaped test piece before applying the slurry, and use it as the mass (g) before the test.
[0189] The slurry was prepared by mixing 6 parts by mass of frog clay, 5 parts by mass of bentonite, and 70 to 100 parts by mass of water with 100 parts by mass of the antioxidant for heating the alloy material. The obtained slurry was applied to the entire surface (upper surface, lower surface, and four side surfaces) of the plate-shaped test piece using a brush and then dried.
[0190] The heating process was simulated by heating the plate-shaped test piece at 1200°C for 2 hours. As for the atmosphere, LNG combustion was simulated. Specifically, the atmosphere gas was adjusted so that the composition of the atmosphere gas became 2-3% O2, 8-10% CO2, 15-20% H2O and the balance N2. The oxide scale attached to the plate-shaped test piece due to heating was immersed in an alkaline aqueous solution and then further immersed in a citric acid aqueous solution to remove it. The mass (g) of the plate-shaped test piece after the oxide scale was removed was measured as the mass (g) after the test.
[0191] The difference between the mass (g) of the plate-shaped test piece before heating and the mass (g) of the plate-shaped test piece after heating is divided by the surface area (top surface and four side surfaces) of the plate-shaped test piece (1200 mm 2 ), and the value thus obtained is taken as oxidation loss. The oxidation loss is 0.200 g / mm 2 The following test pieces were judged to be excellent in oxidation resistance.
[0192] [Test results]
[0193] In Test No. 2-2, since the composition of the compound is appropriate, the softening point of the antioxidant for heating the alloy material is 800° C. or higher. As a result, the oxidation loss of the antioxidant for heating the alloy material in Test No. 2-2 is 0.200 g / mm 2 Below, the oxidation resistance is excellent.
[0194] On the other hand, in Test No. 2-1, no antioxidant for heating the alloy material was used. Therefore, the oxidation loss was higher than 0.200 g / mm 2 , poor oxidation resistance.
[0195] In test number 2-3, the total content of Na2O, K2O and CaO is low. Therefore, the softening point is less than 800°C. Therefore, the fluidity of the antioxidant for heating the alloy material is low. As a result, the oxidation loss is higher than 0.200 g / mm 2 , poor oxidation resistance.
[0196] In test number 2-4, the Na2O content was high. Therefore, the Cr2O3 film as a protective film was dissolved. As a result, the oxidation loss was higher than 0.200 g / mm 2 , poor oxidation resistance.
[0197] [Blocking resistance evaluation test]
[0198] Prepare the antioxidant for heating the alloy material shown in Table 3. Test numbers 3-1 to 3-5 are the compositions described in Table 3. In test number 3-3, the total amount of each component described in Table 3 is 100% by mass. In test numbers 3-1, 3-2, 3-4 and 3-5, the total amount of each component described in Table 3 is less than 100% by mass, and the remainder is impurities. The composition of the antioxidant for heating the alloy material is obtained by drying and performing ICP analysis after manufacturing the antioxidant for heating the alloy material. Specifically, the contents of Si, Al, Mg, Na, K, Ca and B obtained by ICP are converted into the contents of SiO2, Al2O3, MgO, Na2O, K2O, CaO and B2O3, respectively, and the contents of each component are calculated. It should be noted that test number 3-1 is the same as test number 1-1. Test number 3-2 is the same as test number 1-4. Test number 3-3 is the same as test number 2-2.
[0199] [Table 3]
[0200]
[0201] Prepare a plate-shaped test piece to simulate the alloy material. The plate-shaped test piece uses a duplex stainless steel material equivalent to A240UNS S39274 specified in ASTM. The dimensions of the plate-shaped test piece are 4 mm thick, 25 mm long, and 80 mm wide. The slurry is generated by mixing 6 parts by mass of frog clay, 5 parts by mass of bentonite, and 70 to 100 parts by mass of water with 100 parts by mass of an antioxidant for heating the alloy material. Use a brush to apply the resulting slurry to the 25 mm × 20 mm surface at the end of the 25 mm × 80 mm surface as the upper surface of the plate-shaped test piece, and then dry it. Overlap two plate-shaped test pieces in such a way that the slurry-coated surfaces are in full contact with each other.
[0202] The plate-shaped test piece coated with the antioxidant for heating the alloy material was heated at 1300° C. for 2 hours in an air atmosphere.
[0203] After heating, the two plate-shaped test pieces were evaluated for adhesion. Fig.11 This is a schematic diagram of an apparatus for evaluating blocking resistance. Fig.11 Specifically, refer to Fig.11 , a metal rod 100 is pre-fixed at the end of one of the two plate-shaped test pieces A by welding. The plate-shaped test piece A welded with the metal rod 100 is overlapped with the other plate-shaped test piece B in such a way that the slurry-coated surfaces are in full contact with each other. The plate-shaped test piece B is fixed in a tubular furnace 110 by means of a fixing tool 120. The metal rod 100 is pulled in a horizontal direction, and the adhesion force F (kg) when the two plate-shaped test pieces are peeled off in a direction horizontal to the surface of 25 mm × 80 mm is measured. For the determination of the adhesion force, a digital crane scale TDTB-25 manufactured by TRUSCO Zhongshan Co., Ltd. is used. The heating temperature of the test piece during the measurement is 1300°C, the measurement environment is an atmospheric atmosphere, and the tensile speed is 10 to 20 cm / second. The results are shown in the "Adhesion (kg)" column in Table 3.
[0204] [Test results]
[0205] Referring to Table 3, the content of each component in the antioxidant for heating alloy materials of test numbers 3-1 to 3-3 and 3-5 is appropriate and satisfies formula (1). Therefore, the adhesive force when the two plate-shaped test pieces are peeled off is 2.60 kg or less. The antioxidant for heating alloy materials of test numbers 3-1 to 3-3 and 3-5 has excellent anti-blocking properties.
[0206] On the other hand, in the antioxidant for heating alloy materials of test number 3-4, the contents of each component are appropriate, but do not satisfy formula (1). Therefore, the adhesion when the two plate-shaped test pieces are peeled off is 2.84 kg. The antioxidant for heating alloy materials of test number 3-4 has poor anti-blocking property.
[0207] [Example 2]
[0208] [Dustproof evaluation test]
[0209] The antioxidants for heating the alloy materials of the test numbers 1-1 and 1-2 in Table 1 were prepared. The test pieces were steel materials of JIS SUS312L.
[0210] The slurry of the antioxidant for heating the alloy material of the test number 1-1 in Table 1 is applied to the steel material. The slurry of the antioxidant for heating the alloy material is prepared by mixing 6 parts by mass of frog clay, 5 parts by mass of bentonite, and 70 to 100 parts by mass of water with respect to 100 parts by mass of the antioxidant for heating the alloy material. After applying the obtained slurry to the surface (upper surface, lower surface and four side surfaces) of the steel material, it is dried and subjected to a uniform heat treatment. The uniform heat treatment is carried out at 1270°C for 50 hours. During the uniform heat treatment, exhaust gas is recovered from the chimney of the uniform heat furnace every hour. The amount of exhaust gas recovered is measured using an exhaust gas measuring device. Furthermore, the weight of the white solid matter in the recovered exhaust gas is measured as coal ash. The weight of the coal ash (white solid matter) relative to the exhaust gas per unit volume is calculated as the coal ash generation amount (mg / m 3 During the heat treatment, the above test was performed every 1 hour for a total of 50 times, and the resulting coal ash generation amount (mg / m 3 ) is set to the maximum value of the coal ash generation amount (mg / m 3 ). For the heating antioxidant for the alloy material of test number 1-2 in Table 1, a dustproof evaluation test was carried out using the same method as the heating antioxidant for the alloy material of test number 1-1 in Table 1. Regarding the heating antioxidant for test number 1-2, the slurry generated in the same proportion as that of test number 1-1 was also applied to the surface (upper surface, lower surface and four side surfaces) of the steel material. For the steel material coated with the heating antioxidant for the alloy material of test number 1-2, a heat treatment was performed in the same manner as in test number 1-1. Regarding the heating antioxidant for the alloy material of test number 1-2, the amount of coal ash generated during the heat treatment was calculated in the same manner as in the case of using the heating antioxidant for the alloy material of test number 1-1. The results are shown in Fig.10 .
[0211] Compared with the antioxidant for heating alloy materials of Test No. 1-2, the antioxidant for heating alloy materials of Test No. 1-1 generates significantly less coal ash and is excellent in dust prevention.
[0212] The above is a description of the embodiments of the present invention. However, the above embodiments are merely examples for implementing the present invention. Therefore, the present invention is not limited to the above embodiments, and can be implemented by appropriately changing the above embodiments within the scope of the gist thereof.
[0213] Description of Reference Numerals
[0214] 1 Abnormal oxidation
[0215] 2 Cr2O3 coating
[0216] 3 Oxide scale with Fe as the main component
[0217] 4 Oxide scale mainly composed of Fe and Cr
[0218] 10. Base material
[0219] 20 base material
[0220] 30 base material
Claims
1. An antioxidant for heating an alloy material, which contains, in terms of mass %, SiO2: 40.0~80.0%, Al2O3: 0~30.0%, MgO: 0-5.0%, Na2O: greater than 0% and less than 6.0%, K2O: more than 0% and less than 20.00%, CaO: more than 0% and 25.0% or less, and B2O3: 0% or more and less than 0.5%, Furthermore, the total amount of Na2O, K2O and CaO is 10.00 to 50.00%, The remainder consists of impurities and satisfies equation (1), (2SiO2+Al2O3) / (0.1MgO+0.2B2O3+6Na2O+1.4K2O+2CaO)≤2.50 (1) Here, the content of the corresponding component in mass % is substituted into each chemical formula in formula (1).
2. A method for heating an alloy material, comprising: A step of applying the antioxidant for heating the alloy material according to claim 1 to the surface of the alloy material; and A step of heating the alloy material coated with the antioxidant for heating the alloy material.
3. The method for heating an alloy material according to claim 2, wherein: The chemical composition of the alloy material contains 12 to 50 mass % of Cr.
4. The method for heating an alloy material according to claim 3, wherein: The chemical composition of the alloy material contains 1 to 15 mass % of Mo.
5. The method for heating an alloy material according to any one of claims 2 to 4, wherein: In the heating step, the alloy material coated with the alloy material heating antioxidant is heated at a temperature of 1000 to 1350° C. for 15 to 50 hours.
Citation Information
Patent Citations
Preventing method for edge crack in rolling work for steel
JP1981026603A
Antioxidant for high temperature use for steel stock
JP1990209420A
Method for preventing high-temperature oxidation of metallic material
JP1991291325A
Antioxidant for steel strip
JP1992072011A
Method and apparatus for continuously annealing stainless steel strip
JP1992072019A